Increasing the accuracy and reliability of the Digital Kreybig Soil Information System - Pásztor, László; Szabó, József; Bakacsi, Zsófia; Dombos, Miklós; László, Péter (Acta Agraria Kaposváriensis, 2007)
A key issue of applicability of both traditional soil maps and spatial soil information systems (SSIS) is their accuracy. The „raw” SSIS, which consists of scanned map sheets, vectorized spatial data (soil units as polygons and soil profiles as points) and profile database can be mainly considered as the digitally converted version of the processed map-based soil information. Nevertheless, there are various opportunities for increasing both its spatial and thematic accuracy, which is also a duty of the data owner/manager. The integration of spatial soil information within appropriate spatial data infrastructure (SDI) and the consideration of the characteristics of the original survey support this process. In the present paper we are presenting our results acquired in the inherent refinement and upgrading of the Kreybig Digital Soil Information System (KDSIS) originating from the 1:25,000 scale practical soil mapping of Hungary.
Keywords: spatial soil information system; spatial data infrastructure; reambulation